2006
DOI: 10.1111/j.1399-3054.2006.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the genetic understanding of plant iron and zinc nutrition

Abstract: In this review, we describe the need and progress to improve the iron and zinc contents in crop plants by genetic means. To achieve this goal either by transgenic approaches or classical breeding, knowledge about the physiological and molecular mechanisms of mineral uptake and mineral homeostasis will be very helpful. The progress in our understanding of the molecular processes and genes is described, and the use of the identified genes by transgenic approaches is illustrated. Genetic mapping of the existing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 89 publications
1
98
0
1
Order By: Relevance
“…In addition to the physiological mechanisms involved in the uptake, distribution, and accumulation of Fe and Zn in seed (Borg et al 2009;Cakmak et al 2010), the use of genes (L€ onnerdal 2003;Vasconcelos et al 2003;Ghandilyan et al 2006;Brinch-Pedersen et al 2007;Waters et al 2009;Sperotto et al 2010), and chelating agents such as EDTA (Nowack et al 2008) have been reported to enhance efflux of nutrients including Fe and Zn from the vegetative tissues to seed of crops.…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…In addition to the physiological mechanisms involved in the uptake, distribution, and accumulation of Fe and Zn in seed (Borg et al 2009;Cakmak et al 2010), the use of genes (L€ onnerdal 2003;Vasconcelos et al 2003;Ghandilyan et al 2006;Brinch-Pedersen et al 2007;Waters et al 2009;Sperotto et al 2010), and chelating agents such as EDTA (Nowack et al 2008) have been reported to enhance efflux of nutrients including Fe and Zn from the vegetative tissues to seed of crops.…”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…It is a main source of mineral nutrients for the Chinese population (Ma et al 2007), and therefore elevating the amount of beneficial minerals in Chinese cabbage can contribute to the reduction of micronutrient malnutrition in China. The improvement of mineral content by plant breeding, also referred to as biofortification (Bouis 2002), is a recent development that requires knowledge about the genetic variation for this trait and genetic markers linked to relevant genes (reviewed in Ghandilyan et al 2006). However, genetic studies on mineral content in crops have been limited mainly to seeds, such as for common bean (Beebe et al 2000;Islam et al 2002), rice (Gregorio et al 2000), wheat (Monasterio and Graham 2000), maize (Banziger and Long 2000) and also the model species Arabidopsis thaliana (Vreugdenhil et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mineral deficiency results in poor health and higher rates of mortality, and it permanently impairs the cognitive abilities of infants (1). Although plant-derived foods contain a wide variety of micronutrients, their levels are usually too low to meet daily needs (2). Therefore, various means for micronutrient biofortification have been attempted through breeding and transgenic approaches (3).…”
mentioning
confidence: 99%